Appeals - Estabrook, Samantha K. (Kansas State University, 2019)
Appellate zoning boards provide aggrieved property owners the ability to appeal bulk zoning regulations which otherwise create an undue hardship on the property owner. However, this process when not monitored, can create the following three primary, twentieth-century criticisms: (1) a high number of cases paired with high rates of approval, (2) applicant properties which lack uniqueness, and (3) the ability to issue conditional use permits (Bryden, 1977; Leary, 1957). In order to test if the three criticisms are relevant in twenty-first-century practices, the research developed a record system for reviewing all state statutes; records and analyzes the actions of appellate zoning boards in ten Kansas municipal governments from 2014-2018, and focuses on the decision trends and themes of Manhattan, Kansas, an appellate zoning board currently subject to criticism. Document analysis, coding, and tracking are used to analyze 676 cases and reveal varying trends and themes among Kansas municipal governments. The most significant finding is that Manhattan’s Board of Zoning Appeals out-paces peer municipal governments with a 17% higher rate of approval, 11% of approved cases fail to meet the uniqueness of property standard and a nearly 10% difference in the percentage of cases paired with conditional use permits. These findings support the validity of twentieth-century criticisms of appellate zoning boards and provide Manhattan, Kansas as a case of potential misuse of appellate zoning statutes.
Keywords: Board of zoning appeals; Appellate zoning board; Record keeping